Case Presentation - Biventricular Hypertrophy and Valvular Pulmonary Stenosis in Adult Patient with Noonan Syndrome: A Rare Case - Tinton Pristianto; Rosi Amrilla Fagi (Cardiovascular and Cardiometabolic Journal, 2021)
Introduction: Noonan syndrome (NS) is a genetic disorder often accompanied by multiple congenital abnormalities. The prevalence of NS at live birth has been reported as one in 1000-2500 individuals. About 80% of patients with Noonan syndrome have abnormalities in the cardiovascular system. Case presentation:41-year-old Javanese male presented with chief complaint shortness of breath.  His Body Mass Index (BMI) was 18,3. He had an oval-shaped face with a short neck, thin hair, and prominent nasolabial fold. Echocardiography showed biventricular hypertrophy alongside pulmonary valve stenosis, pulmonary regurgitation and minimal pericardial effusion. Discussion: In 1962, Jacqueline Noonan, a pediatric cardiologist, identified 9 patients whose faces were very similar, had short stature, significant chest deformities, and with pulmonary stenosis. Noonan syndrome is a relatively common non-chromosomal syndrome that is similar to the phenotype of Turner's syndrome and presents with cardiovascular malformations. Adult with NS has distinctive facial features such as ptosis, wide eyes, low posterior rotation of ears and helical thickening, and a wide neck.Pulmonary stenosis is the most common heartdefect found in NS, besides HCM isalsoquitecommon inabout20% of patients. We reported a case of a patient with typical characteristics of NS such as pulmonary valve stenosis accompanied by biventricular ventricular hypertrophyand its typical face who survived through adulthood. Conclusion: Syndrome Noonan in the adult is quite rare and difficult to diagnose. We reported a case of an adult man with facial appearance and echocardiographic findings identical with Noonan Syndrome. Keywords: Adult, Biventricular hypertrophy, Noonan Syndrome, Pulmonary valve stenosis